2013
DOI: 10.1042/bj20121373
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of amphiphysins with AP-1 clathrin adaptors at the membrane

Abstract: The assembly of clathrin/AP (adaptor protein)-1-coated vesicles on the trans-Golgi network and endosomes is much less studied than that of clathrin/AP-2 vesicles at the plasma membrane for endocytosis. In vitro, the association of AP-1 with protein-free liposomes had been shown to require phosphoinositides, Arf1 (ADP-ribosylation factor 1)-GTP and additional cytosolic factor(s). We have purified an active fraction from brain cytosol and found it to contain amphiphysin 1 and 2 and endophilin A1, three proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Neuronal BIN1 has been previously involved in neurite growth, presynaptic cytoskeleton structural integrity, and fission of synaptic vesicles in neurons[11,12,17,19]. Furthermore, mice lacking Amphiphysin I and Bin1 in neurons showed defects in synaptic vesicle recycling, increased mortality, major learning deficits and higher propensity to seizure[11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal BIN1 has been previously involved in neurite growth, presynaptic cytoskeleton structural integrity, and fission of synaptic vesicles in neurons[11,12,17,19]. Furthermore, mice lacking Amphiphysin I and Bin1 in neurons showed defects in synaptic vesicle recycling, increased mortality, major learning deficits and higher propensity to seizure[11].…”
Section: Discussionmentioning
confidence: 99%
“…BIN1 is expressed in at least 12 different isoforms generated by alternative splicing[10]. BIN1 isoform 1, exclusively expressed in neurons[17,18], is involved in neurite growth, presynaptic cytoskeleton structural integrity, and fission of synaptic vesicles in neurons[11,12,17,19]. Interestingly, BIN1 -also called Amphishysin II[8]- interacts with Amphiphysin I in neurons[18].…”
Section: Introductionmentioning
confidence: 99%
“…A member of the Bin/Amphiphysin/Rvs (BAR) family of adaptor proteins that regulates lipid membrane dynamics 26,27 , BIN1 is ubiquitously expressed throughout the body, with the highest expression in skeletal muscle 28 , followed by the brain 29,30 . BIN1 is involved in a wide range of cellular functions associated with membrane curvature, including phagocytosis and clathrin-mediated endocytosis 26,27,31,32 .The genetic association between BIN1 and AD prompted examination of the role of BIN1 in the CNS. In the brain, BIN1 is expressed in multiple isoforms: the ubiquitously expressed isoforms 9 and 10, together with brain-specific isoforms 1 through 7 26,27,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence the BIN1iso1-induced degeneration depends on its CLAP domain and to a lesser extent on the Exon7 in the BAR domain. Since the CLAP domain is known to interact with AP-1 adaptin, AP-2 adaptin and the Clathrin Heavy Chain, which are involved in endocytosis and intracellular trafficking (Huser et al, 2013; Ramjaun and McPherson, 1998; Wigge et al, 1997), this suggested that the cause of the degeneration could be a defect in endocytosis/intracellular trafficking.…”
Section: Resultsmentioning
confidence: 99%